DIRECT AND INDIRECT INFLUENCE FACTORS OF MSME MARKETING PERFORMANCE IN CIKARANG - Darius S, Daniel On; Tanjung, Agustini (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
This study assessed the impact of creativity, digital marketing and marketing capabilities on the performance of MSMEs, focusing on competitive advantage and government policies. This research employs quantitative research methods. The population under investigation in this study was constituted by micro, small and medium enterprises operating in the snack food sector in Cikarang, with a sample size of 217 respondents. The sampling method employed was random, with data collected via questionnaire. This study shows that creativity, digital marketing and competitive advantage affect marketing performance, while marketing capability has no effect. Both creativity and capability affect competitive advantage, while digital marketing has no effect. The results show that competitive advantage can affect marketing performance through creativity and capability. However, it cannot affect marketing capability and performance. Government policy can affect the relationship between creativity and digital marketing, but not between marketing capability and competitive advantage.